Measurements of Quality of Life and Per-capita Income in Nepal - Shakya, Kushum (Economic Journal of Nepal, 2015)
The quality of life is major factor for economic development. This paper explores two main aims firstly it shows the measurements of quality of life as changes in parameters, secondly it shows the relationship between parameters of PQLI and per capita income. The quality of life measured by physical quality of life index (PQLI), which is an average of age at birth at one, literacy rate since 15 and above and infant mortality. Further, this article shows the improved version of the measurement of PQLI, since the pace of development is changed or the life expectancy and infant mortality have been improved than as assumed in the PQLI technique. The value of PQLI lies between 0-100. The value of PQLI has been calculated in highly, medium and low developed, SAARC countries and Nepal separately. Therefore, the article highlights the calculation of PQLI based on the development of the country and also found that the value of PQLI has been improved. Finally, the article shows the relationship of quality of life and per capita income as well. And, it concludes that higher the quality of life higher the per capita income.The Economic Journal of Nepal, Vol. 35, No. 2, April-June 2012 (Issue N0. 138)